Chemical Fingerprint Using FTIR and HPLC as Qualitative Analysis in the Study of Propagation of Labisia pumila Var. Alata (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Labisia pumila, known as kacip fatimah is a traditional herbs widely used for women. The herb was used as a post partum medicine to help contract the birth channel. From previous research, 120 clones of Labisia pumila var. alata was collected from three different locations and 30 clones of the herbs was found having high yielding of total phenolic content (TPC). In this study, one clone from each location was selected for further analyses, which are TA14 from Kuala Berang, TSA13 from Kemaman and DA20 from Gua Musang. Fourier Transform Infrared spectroscopy (FTIR) associated with second derivative infrared spectroscopy was applied to identify the chemical fingerprint of each clone of Labisia pumila. This analytical method is highly rapid and effective for analysis of medicinal herbs. Second derivative IR spectroscopy could enhance the spectral resolution by amplifying tiny differences in the IR spectrum. In this method, the whole chemical property of the sample can be revealed and shown in the IR spectrum. A total of ten absorption peaks were obviously present in the IR spectra which can be used to characterize the species. The IR spectra shows the presence of broader peak at frequencies of range 3266 – 3338 cm-1 which attributable to the alcohol group. This study also attempts to develop HPLC fingerprint of the selected clones. Observation on HPLC spectra shows the presence of one distinct peak at retention time of 12.30, 12.99 and 12.93 min, respectively in each clone. This compound will be characterized and will be used as reference compound in quality assessment in plant breeding
Keywords: Labisia pumila; Fourier Transform Infrared spectroscopy (FTIR); second derivative infrared spectroscopy; macroscopic fingerprint; High Performance Liquid Chromatography (HPLC)